The outcomes of bilateral bone conduction hearing devices (BCHD) implantation in the treatment of hearing loss: A systematic review. (4th March 2022) - Heath, Ella; Dawoud, Moustafa Mohamed; Stavrakas, Marios; Ray, Jaydip
Abstract : Objectives: Bone Conduction Hearing Devices (BCHDs) are a means of improving hearing ability in those that do not receive full benefit from conventional hearing aids. In 2016, the NHS started commissioning bilateral BCHDs. This review aims to evaluate the current literature and identify areas for further research. Methods: This review was conducted in line with the PRISMA guidelines and registered on the PROSPERO database (registration CRD42020191956). MEDLINE, CINAHL and The Cochrane Library were systematically searched. The full text of relevant titles and abstracts was then reviewed before data extraction was undertaken. Risk of bias was assessed using the ROBINS-1 tool. Results: Searches identified 125 studies. After removing duplicates, 28 full texts were screened. 14 studies were included in the final review. Amongst the audiological outcomes, greater improvements for bilateral compared to unilateral BCHDs were seen in hearing thresholds, understanding speech in quiet, localization, and restoration of binaural hearing. Thus, supporting the addition of a second implant. For speech in noise however, bilateral BCHDs were less effective when the noise was presented from one side. Increases in measures of Quality of Life, including the Glasgow Benefit Index, were seen across all included studies. No studies included complication rates. Conclusion: Overall, bilateral BCHDs offer benefits to the recipient's audiological capabilities and QoL. However, more research is required on the complications and the cost of bilateral BCHDs. Further to this, future research should aim to use uniform tests to measure outcomes.